Role of Circulating Tumor DNA in Adapting Immunotherapy Approaches in Breast Cancer - Sudhir Kumar; Rossanna C. Pezo (Current Oncology, 2025)
Immunotherapy has a defined role in the treatment of both early- and late-stage triple-negative breast cancer (TNBC) and is under active exploration in human epidermal receptor 2-positive as well as high-risk hormone-receptor-positive subtypes. It is critical to balance the efficacy and toxicity of immunotherapy while keeping the cost and duration of treatment in check. In addition to the immunohistochemistry testing of PD-L1 expression, which only predicts the efficacy of immunotherapy in metastatic TNBC, there is a lack of biomarkers that are better standardized to predict efficacy and treatment response, detect early relapse, and guide prognosis in breast cancer patients treated with immunotherapy. Circulating tumor DNA (ctDNA) is a minimally invasive, dynamic, real-time, blood-based biomarker that has shown promising value in the management of solid tumors, including breast cancer. This review discusses the emerging evidence for the potential application of ctDNA to further refine patient-centered care and personalize treatment based on a molecularly defined risk assessment for breast cancer patients treated with immunotherapy-based approaches. We further discuss the challenges and barriers to widespread adoption of this promising tool in the management of breast cancer patients requiring immunotherapy.